INTEGRATING SUSTAINABILITY INTO MANAGEMENT ACCOUNTING PRACTICES: EVIDENCE FROM INDONESIAN MANUFACTURING FIRMS - Nida Garnida Fitrianti; Anggun Yolistina; Raden Roro Fatmasari (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Background: Indonesian manufacturing firms face mounting pressure to integrate environmental considerations into business operations amid growing stakeholder expectations and regulatory requirements. While traditional management accounting focuses primarily on financial performance, sustainability integration demands broader metrics encompassing environmental and social dimensions. Aims: This study investigates sustainability integration into management accounting systems across Indonesian manufacturing firms examining current adoption patterns, organizational factors influencing integration, specific practices employed, and relationships between sustainability accounting sophistication and performance outcomes. Research Method: A convergent mixed-methods design combined survey analysis of 156 manufacturing firms with in-depth case studies of 12 organizations. Statistical analysis utilized hierarchical regression while qualitative data underwent thematic coding. Results and Conclusion: Three distinct integration archetypes emerged: Compliance-Driven firms (38%), Strategic Adopters (29%), and Pioneering Transformers (33%). Advanced integration correlates significantly with superior environmental performance (24-31% improvements) and enhanced financial outcomes (12-18% cost savings). Regulatory pressures (β=0.34), customer requirements (β=0.41), and organizational capabilities (β=0.38) emerge as significant drivers. Contribution: This research extends management accounting literature by empirically demonstrating sustainability integration patterns in emerging market manufacturing contexts. Findings provide practical guidance for firms pursuing sustainability accounting adoption and inform policy interventions supporting sustainable industrial development.